An Analysis of Translation Strategies on Idioms Found in Novel Harry Potter and The Philosopher’s Stone - Bloner Sinurat; Dian Jessica Noventy Sigalingging; Narambean Simanjuntak; Herman; Febrika Dwi Lestari Lumbantoruan (Global Scientific Publishing, 2022)
This research aims to analyze the translation strategies in idioms found in the novel Harry Potter and The Philosopher's Stone. Translating an idiom is not an easy task. To translate idioms, a strategy is needed to translate them, especially in translating idiom expressions in a novel. Idiomatic translation strategy is a way that translators use to translate an idiomatic expression. This research used qualitative research. The instrument of collecting data used documentation and documents data collection. The data of this research are idioms, and the source data is taken from the novel Harry Potter and the Philosopher's Stone. The result of the research shows that there are three types of idioms namely pure idioms, semi-idioms, and literal idioms. There are four types of idiom translation strategies, namely using idioms of similar meaning and form, using idioms of similar meaning but dissimilar form, translation by paraphrasing and translation by omission. Based on the results of data analysis that had been obtained, the most dominant idiom translation strategy used by translators in chapters one and two is translation by paraphrasing with a total of 8 data (57%), then idiom of similar meaning but dissimilar form 3 data (22%), translation by omission 2 data (14%), and using the idiom of similar meaning and form 1 data (7%). For the most dominant type of idiom, pure idiom is 6 data, semi-idiom is 4 data, and literal idiom is 3 data.
Keywords: Translation; Idiom; language; Target